The history of Eurocurrency system: future prospects and implications for the south african foreign exchange market - Bell, Graham Douglas (My University, 2015)
BELL, Graham Douglas, M.Com. University of the Witwatersrand, 1985. This dissertation studies the development and operation, advantages and problems associated with the Eurocurrency market. It also considers the parallel emergence of the United States dollar as the primary international vehicle currency. A well-developed international money market with easy access to a widely accepted international numeric is deemed desirable because it reduces the costs of international financial transactions and facilitates international capital mobility. Two major criticisms are that the Eurocurrency market contributes to international inflation and that Euro banks have been imprudent in lending to developing countries. The thesis concludes that the conventional credit multiplier model is not appropriate in studying the market but that there is, however, some inflationary potential. As for imprudent Euro bank lending, some blame adheres to the bankers but extensive international controls are ruled out. Finally, the advent of floating exchange rates in the 1970s and uncertainty surrounding United States economic policy has led to considerable uncertainty in international financial markets. This has been aggravated by volatile short-term international capital flows fuelled by the efficient Eurocurrency market. In such an environment South Africa has experienced considerable oscillations in the price of gold, its major export, and has embarked on a programme to establish a flexible foreign exchange market. Much progress has been made but important changes, particularly in the forward market, are vital.